Save your Baby, Save Ten Percent: National Baby Week, The Infants' Department, and the Modern Pregnant Woman, 1905-1925 - Lemus, Cheryl (Journal of Women's History, 2013)
This article examines how merchants created separate infants' departments in stores and promoted events such as National Baby Week. Retailers took part in molding the expectations attached to the purchase of baby goods, but they relied on the medical profession to help. Department stores and other retailers invited physicians to lecture on prenatal care, hired nurses to advise prospective mothers, and trained sales staff in the latest medical advice and findings. Medical professionals and retailers worked together to educate the expectant mother as to her responsibilities as a patient and as a consumer. However, retailers also began to suggest that the consumer role was an important indicator of a woman's future role as mother, claiming that when she visited her favorite department store, the modern pregnant woman publicly demonstrated her readiness for motherhood.
Keywords: Business History and gender